2014
DOI: 10.5098/hmt.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal and Solutal Stratification on Mixed Convection Flow Along a Vertical Plate Saturated With Couple Stress Fluid

Abstract: The effect of heat and mass stratification on mixed convection along a vertical plate embedded in a couple stress fluid has been presented. The nonlinear system of equations with appropriate boundary conditions is primarily reduced to non-dimensional form by pseudo-similarity transformations. Keller-box implicit finite difference scheme is employed to solve the resultant system of dimensionless equations. The validation of this scheme is shown through the comparison between the present and available literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Chakraborty et al (2016) obtained numerical solution with convective boundary conditions for bio convection of a nanofluid flow. Extensive discussion of other applications recently studied by several researchers over stretching sheet which includes Sisko fluid flow employing Homotopy Analysis Method (HAM) Khan and Shahzad (2012), Second grade MHD fluid flow using Runge-Kutta (RK) sixth order integration scheme Das et al (2016), considered semi-infinite inclined and ideally transparent flat plate embedded in a porous medium with an Implicit finite difference scheme (IFDM), mixed convective couple stress fluid flow in a vertical channel with HAM by Kaladhar and Srinivasacharya (2014) and Prandtl-Eyring fluid flow with Keller-Box Method (KBM) Hussain et al (2017). Further a significant amount of research on Newtonian and non-Newtonian fluid flows over stretching sheet were found in (Akbar et al, 2016;Kumar et al, 2017;Chamkha et al, 2010;Reddy and Gorla, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty et al (2016) obtained numerical solution with convective boundary conditions for bio convection of a nanofluid flow. Extensive discussion of other applications recently studied by several researchers over stretching sheet which includes Sisko fluid flow employing Homotopy Analysis Method (HAM) Khan and Shahzad (2012), Second grade MHD fluid flow using Runge-Kutta (RK) sixth order integration scheme Das et al (2016), considered semi-infinite inclined and ideally transparent flat plate embedded in a porous medium with an Implicit finite difference scheme (IFDM), mixed convective couple stress fluid flow in a vertical channel with HAM by Kaladhar and Srinivasacharya (2014) and Prandtl-Eyring fluid flow with Keller-Box Method (KBM) Hussain et al (2017). Further a significant amount of research on Newtonian and non-Newtonian fluid flows over stretching sheet were found in (Akbar et al, 2016;Kumar et al, 2017;Chamkha et al, 2010;Reddy and Gorla, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sugunamma et al [15] analyzed inclined magnetic field and chemical reaction effects on flow over a semi infinite vertical porous plate through the porous medium. Effects of thermal and solutal stratification for a couple stress fluid along a vertical plate on mixed convection analyzed by Kaladhar and Srinivasacharya [16]. Sreenadh et al [17] and Kaladhar [18] studied MHD, radiation and Soret effects of a couple stress fluid through a vertical porous stratum on a mixed convection.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivasacharya and Kaladhar (2012a) analyzed Hall and Ion-Slip effects on mixed convection flow of couple stress fluid between parallel vertical plates. Later Kaladhar and Srinivasacharya (2014) established the effects of thermal and also solutal stratification on free and forced convection flow over a vertical plate flooded with couple stress fluid. Srinivas and Ramana Murthy (2015) analyzed and discussed thermodynamic MHD flow of two immiscible micropolar fluid between two parallel plates.…”
Section: Introductionmentioning
confidence: 99%